(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
Preliminary study of the Private Insurance and Reinsurance Intermediation Act26/2006, that transposes to Spanish Law the Directive 2002/92/CE. This Act containsa new regulation on insurance intermediaries (exclusive agents, linked agents, bank-insurance operators, brokers and reinsurance brokers) and rules on protection of insurance consumers.